Mechanisms of Resistance to Folate Pathway Inhibitors in Burkholderia pseudomallei: Deviation from the Norm - Nicole L. Podnecky (American Society for Microbiology, 2017)
ABSTRACT The trimethoprim and sulfamethoxazole combination, co-trimoxazole, plays a vital role in the treatment of Burkholderia pseudomallei infections. Previous studies demonstrated that the B. pseudomallei BpeEF-OprC efflux pump confers widespread trimethoprim resistance in clinical and environmental isolates, but this is not accompanied by significant resistance to co-trimoxazole. Using the excluded select-agent strain B. pseudomallei Bp82, we now show that in vitro acquired trimethoprim versus co-trimoxazole resistance is mainly mediated by constitutive BpeEF-OprC expression due to bpeT mutations or by BpeEF-OprC overexpression due to bpeS mutations. Mutations in bpeT affect the carboxy-terminal effector-binding domain of the BpeT LysR-type activator protein. Trimethoprim resistance can also be mediated by dihydrofolate reductase (FolA) target mutations, but this occurs rarely unless BpeEF-OprC is absent. BpeS is a transcriptional regulator that is 62% identical to BpeT. Mutations affecting the BpeS DNA-binding or carboxy-terminal effector-binding domains result in constitutive BpeEF-OprC overexpression, leading to trimethoprim and sulfamethoxazole efflux and thus to co-trimoxazole resistance. The majority of laboratory-selected co-trimoxazole-resistant mutants often also contain mutations in folM, encoding a pterin reductase. Genetic analyses of these mutants established that both bpeS mutations and folM mutations contribute to co-trimoxazole resistance, although the exact role of folM remains to be determined. Mutations affecting bpeT, bpeS, and folM are common in co-trimoxazole-resistant clinical isolates, indicating that mutations affecting these genes are clinically significant. Co-trimoxazole resistance in B. pseudomallei is a complex phenomenon, which may explain why resistance to this drug is rare in this bacterium. IMPORTANCE Burkholderia pseudomallei causes melioidosis, a tropical disease that is difficult to treat. The bacterium’s resistance to antibiotics limits therapeutic options. The paucity of orally available drugs further complicates therapy. The oral drug of choice is co-trimoxazole, a combination of trimethoprim and sulfamethoxazole. These antibiotics target two distinct enzymes, FolA (dihydrofolate reductase) and FolP (dihydropteroate synthase), in the bacterial tetrahydrofolate biosynthetic pathway. Although co-trimoxazole resistance is minimized due to two-target inhibition, bacterial resistance due to folA and folP mutations does occur. Co-trimoxazole resistance in B. pseudomallei is rare and has not yet been studied. Co-trimoxazole resistance in this bacterium employs a novel strategy involving differential regulation of BpeEF-OprC efflux pump expression that determines the drug resistance profile. Contributing are mutations affecting folA, but not folP, and folM, a folate pathway-associated gene whose function is not yet well understood and which has not been previously implicated in folate inhibitor resistance in clinical isolates.